Enhancing bio - efficacy of Trichoderma spp. for the management of soil borne fungal pathogens - Hima V M (Department of Plant Pathology, College of Horticulture, 2017)
A study on ‘Enhancing bioefficacy of Trichoderma spp. for the management of soil borne fungal pathogens’ was carried out in the Department of Plant Pathology, College of Horticulture, Vellanikkara, during the period 2011- 2016. Soil borne fungal pathogens are the major threat to the farmers for the cultivation of the crops. Estimate showed that 37 per cent of the crop loss was due to pests of which 12 per cent was due to pathogens (Radheshyam et al., 2012). Eventhough, there are various mechanisms including chemicals for the management of soil borne diseases, biocontrol approach is getting wide acceptance because of its broad spectrum activity and eco friendly nature. The ascomycetous fungus, Trichoderma spp. based bio control products share 60 per cent of all fungal based products in the global market. Taking the high potentiality of this fungus in the management of soil borne fungal pathogens, the present study was conducted. Purposive sample surveys were conducted in Kerala state and collected 51 rhizosphere soil samples from different locations of northern, central and southern zones of Kerala including Wayanad. A total of 128 isolates of Trichoderma spp. were isolated from the collected soil samples and were named as Tr 1 to Tr 128. The estimation on soil pH revealed that the occurrence of Trichoderma spp. was more in the pH range of 5.5 - 6.5. Six important soil borne fungal pathogens viz., Pythium aphanidermatum, Phytophthora capsici, Fusarium oxysporum f. sp. cubense, Sclerotium rolfsii, Ganoderma lucidum and Rhizoctonia solani were isolated from the diseased specimens of ginger, pepper, banana, pepper, coconut, rice respectively and were selected to study the antagonistic activity. After preliminary screening and dual culture experiments 20 isolates of Trichoderma spp. showed antagonistic efficiency against all the six pathogens were selected. The antagonistic efficiency of native Trichoderma isolates was compared with that of reference biocontrol agents T. viride and T. harzianum released from KAU. All the isolates, except Tr 2 and Tr 109, recorded cellulase activity of 0.5 to 1.0. Based on the above characters, 12 native isolates of Trichoderma spp., Tr 9, Tr 48, Tr 52 and Tr 76 from northern zone, Tr 2, Tr 14, Tr 43 and Tr 86 from central zone and Tr 34, Tr 41, Tr 97 and Tr 109 from southern zone, were selected for the evaluation of their antagonistic efficiency and the plant growth promoting efficiency under pot culture experiment, where ginger was taken as the test crop and P. aphanidermatum as the test pathogen. In the pot experiment, all the treatments recorded > 72 per cent of germination on 1 MAP. After absolute control, plants treated with Tr 43 showed highest number of tillers/plant, height of the plant and the number of leaves/tiller with records of 45, 19.25cm and 6.72 respectively. Compared to control plants, the least incidence of disease was noticed in the treatment Tr 76 (40.12%) which was followed by Tr 43 (32.33%). Out of 12 Trichoderma isolates, five isolates named Tr 43, Tr 76, Tr 9, Tr 41 and Tr 48, expressed better plant growth promotion and disease suppression activity in the pot culture experiment were selected for further study. The compatibility study of these five isolates with the selected fungicides and insecticides revealed that all the isolates tested were found incompatible with fungicides, carbendazim (0.1%), Bordeaux mixture (1%) and the insecticide quinalphos (0.05%). Only the isolate, Tr 9 was found compatible with the fungicide, mancozeb (0.3%). None of the isolates was inhibited by the insecticide, flubendiamide (0.01%). The field evaluation of these isolates was carried out by taking ginger as test crop and P. aphanidermatum as test pathogen. One month after planting, > 69 per cent of germination was noticed in all the treatments. The treatment Tr 43 recorded highest number of tillers of 8.71. The maximum height of tiller (34.02 cm) and number of leaves (8.82) were recorded by the treatment Tr 9. The least incidence of disease over control was recorded by Tr 9 (27.87 %). Among the five isolates, two isolates (Tr 9 and Tr 43) which showed highest bio-efficacy were selected for strain improvement by mutation and protoplast fusion technics. The parental cultures, Tr 9 and Tr 43 were morphologically characterized and were identified from ITCC (Indian Type Culture Collection) IARI, New Delhi as Trichoderma sp. and T. asperellum respectively (I. D No. 9778.15 and 9782.15). The molecular characterization (RAPD and ITS - PCR) of these isolates was carried out and were identified and confirmed as T. erinaceum and T. asperellum respectively. The mutation of parental cultures Tr 9 (T. erinaceum) and Tr 43 (T. asperellum) conducted by the combination of treatment with UV rays and sodium nitrate, yielded 97 isolates. Preliminary screening of these isolates with the pathogen, S. rolfsii resulted in the selection of three out of 23 mutants of Tr 9 and six out of 74 mutants of Tr 43. The protoplast fusion of Tr 9 and Tr 43 was carried out by using glucanex as lytic enzyme and poly ethylene glycol as fusagent. Out of 15, five fusant isolates were selected after the preliminary screening with S. rolfsii. The antagonistic efficiency of the selected nine mutants and five fusants were further evaluated with soil borne fungal pathogens, Pythium aphanidermatum, Phytophthora capsici, Fusarium oxysporum f. sp. cubense, Sclerotium rolfsii and Rhizoctonia solani. The two mutants, M40M3 and K80M13 and the two fusants, F2 and F4 which showed better antagonism than their parents and the KAU reference cultures, were further evaluated under the pot and field experiments.In the pot culture experiment, the treatment with the mutant K80M13 exhibited better plant growth by recording 91.67 per cent of germination, 30.17 tillers/plant, 36.63 cm height of tiller and 8.9 leaves /tiller. The least incidence of rhizome rot (27 %) was noticed in the plants treated with K80M13 with a maximum yield of 616.67 g/plant. The estimation of total phenols and defense related enzymes viz., peroxidase (PO), poly phenol oxidase (PPO), and phenyl alanine ammonia lyase (PAL) revealed that there was significant increase in the production of defense molecules among the treatments. The highest content of PO, PAL and total phenol was recorded in the plants treated with mutant K80M13 showed 5.93 min-1 and 29.46 nmol trans cinnamic acid and 9.88 μg per g of fresh tissue respectively. The highest content of PPO was observed in plants treated with the fusant F2 (0.12) which was closely followed by that of mutant isolate K80M13 (0.1). The mutant, K80M13 showed better biometric characters of plants in the field condition. It recorded 90.63 per cent of germination, 39.6 tillers/plant, 36.73 cm height of tiller and 11.45 leaves/tiller. Among all the treatments, K80M13 recorded lowest disease incidence of 13 per cent. The maximum record of yield (3.7 Kg/bed) was also noticed in the treatment K80M13. The morphological and molecular characterization of the mutants (M40M3 and K80M13) and the fusants (F2 and F4) was conducted. The results revealed that the sequences of M40M3 and F2 showed significant homology to genes of T. erinaceum and that of K80M13 and F4 showed homology to genes of T. asperellum. The studies revealed that, the mutants M40M3 (T. erinaceum) and K80M13 (T. asperellum); the fusants F2 (T. erinaceum) and F4 (T. asperellum) and their parents Tr 9 (T. erinaceum) and Tr 43 (T. asperellum) were the promising candidates with significant disease suppression and increased plant growth. Among them, the mutant K80M13 which was identified as Trichoderma asperellum recorded maximum disease suppression (45.83%) and highest yield (43.97%) compared to the reference culture of KAU under field condition. This improved mutant Trichoderma asperellum can be released as an efficient biocontrol agent in future after conducting multi-locational trials and toxicological studies.